Effectiveness of Using the Padlet Application in Extensive Reading Courses for English Language Education Study Program Students at Wiralodra University - Asep Restu Suryana; Widia Tri Puspitasari; Zidna Salma Rizqiya; Ibnudin (Manajia: Journal of Education and Management, 2024)
The development of the use of a Learning Management System (Learning Management System) along with the online learning process during the pandemic which has been going on for more than a year has made the learning system more advanced. Among the many LMS, the padlet platform offers added value, namely an interactive, communicative, and innovative learning model. Padlet is an application that is present as an alternative to online learning during the current pandemic. Padlet can help teachers and students to communicate virtually. The padlet application helps educators in providing material, creating assignments, and discussing related material with students. Padlet media made by the teacher as a result of technical guidance also meet good learning standards. Nonetheless, the use of padlets as an LMS in the future needs to be developed in order to meet the demands of online and remote learning. The method used in this literature study is a qualitative descriptive method, which describes several statements regarding the use of the padlet, the advantages and disadvantages of the application, and some matters that are still related to the mechanism of this padlet application. The results of the study show that, first, there are several ways to use the padlet application. Second, there are advantages and disadvantages to the application. Third, there are several reasons why the padlet application is a recommendation in learning during a pandemic.